A comparative study of accuracy between gene Xpert (cartridge-based nucleic acid amplification test) and line probe assay in retreatment cases of sputum-positive pulmonary tuberculosis - Upendra Kumar; D Dhanalakshmi; G. Sravan Kumar; V. Deepan (MRIMS Journal of Health Sciences)
Background: Many studies have compared the efficacy of Gene Xpert (cartridge-based nucleic acid amplification test [CBNAAT]) and line probe assay (LPA) techniques; however, a systematic and meticulous comparison of these two techniques is lacking. Objective: To study the accuracy of GeneXpert Mycobacterium tuberculosis (MTB)/rifampicin (RIF) assay and LPA in the detection of MTB complex in smear-positive retreatment cases of pulmonary tuberculosis (TB). Materials and Methods: This diagnostic evaluation study was conducted on 300 retreatment cases of pulmonary TB. The patients who were receiving retreatment were identified by sputum for acid fast Bacilli by Ziehl–Neelsen staining method and were instructed to provide sputum samples for CBNAAT and LPA. These sputum samples were then processed for liquid culture as part of the routine diagnostic procedure. Results: Majority of the patients (52.3%) were of 31–45 years of age. Males (56%) were more than females (44%). Most of the cases were relapse (88%). Ninety-three percent were reactive on sputum culture. Seventy percent had RIF resistance on CBNAAT. Isoniazid and RIF resistance was seen in 69.7% on LPA. 23.3% were sensitive on LPA and 7% had isoniazid resistance. The sensitivity, specificity, positive predictive value, and negative predictive for CBNAAT as compared with LPA were 75%, 100%, 100%, and 22.2%, respectively. Conclusion: Both LPA and CBNAAT are equally effective in detecting MTB in the given sputum sample. However, LPA is preferred over can be very helpful as it can point out the Isoniazid (INH) and Rifampicin (RIF) resistant nature of the bacterium.